HELMINTH PARASITES OF GOATS AND SHEEP AT SLAUGHTER HOUSE IN LAFIA, NASARAWA STATE, NIGERIA - Aliyu, A. A.; Maikenti, J. I.; Aimankhu, O. P.; Ayuba, S. O.; Ahmed, H. O.; Haruna, A.; Idris, Abdulrazak Muhammad (FUDMA JOURNAL OF SCIENCES, 2020)
Helminth parasites have been recognized as one of the major constraints to both goat and sheep production in Nigeria and other developing countries. A study aimed to determine helminth parasites of goats and sheep at slaughter in Lafia from June to July 2019. Two hundred fecal samples were collected and analyzed from 100 goats and 100 sheep using the direct smear method. The fecal sample examined revealed an overall prevalence of 155(77.5%), with goat having 80(80.0%), sheep 75(75.0%). Thirteen helminth parasites were found with nematode the most prevalent 103(66.5%), trematode had 35(22.6%), and cestode the least with 17(10.1%) and there was a statistically significant difference among the parasites (P
Keywords: Helminth, Goat and Sheep, Slaughter House, Lafia.